Cybersecurity and Data Privacy Compliance Framework for Human Resource Analytics and Digital Workforce Information Systems - Mayokun Oluwabukola Aduwo; Adaobi Beverly Akonobi; Christiana Onyinyechi Makata (International Journal of Scientific Research in Humanities and Social Sciences, 2024)
The exponential growth of human resource analytics and digital workforce information systems has fundamentally transformed organizational talent management practices, creating unprecedented opportunities for data-driven decision making while simultaneously introducing complex cybersecurity and privacy compliance challenges. This comprehensive study presents a holistic framework for addressing cybersecurity vulnerabilities and ensuring data privacy compliance within human resource information systems, particularly focusing on the protection of sensitive employee data and organizational workforce intelligence. The research methodology employed a mixed-methods approach, combining systematic literature review, case study analysis, and expert interviews to develop a robust theoretical and practical foundation for the proposed framework. The findings reveal that contemporary HR analytics platforms face multifaceted security threats including unauthorized access to personal identifiable information, data breaches affecting employment records, insider threats from privileged users, and compliance violations with international privacy regulations such as GDPR, CCPA, and sector-specific requirements (Chen & Williams, 2023; Rodriguez et al., 2022). The study identifies critical vulnerabilities in existing HR information systems, including inadequate encryption protocols, insufficient access controls, weak authentication mechanisms, and limited audit trail capabilities. Through comprehensive analysis of 47 organizational case studies and interviews with 23 cybersecurity professionals specializing in HR technology, this research establishes that traditional security approaches are insufficient for protecting modern workforce data ecosystems. The proposed Cybersecurity and Data Privacy Compliance Framework for Human Resource Analytics integrates zero-trust architecture principles, advanced encryption methodologies, role-based access controls, continuous monitoring systems, and automated compliance reporting mechanisms. The framework addresses five core dimensions: technical security infrastructure, regulatory compliance alignment, organizational governance structures, employee privacy rights management, and incident response protocols. Key components include implementation of end-to-end encryption for all HR data transmissions, deployment of behavioral analytics for anomaly detection, establishment of granular permission matrices for workforce data access, and development of automated privacy impact assessment tools. Validation of the proposed framework through pilot implementations across diverse organizational contexts demonstrates significant improvements in security posture, with organizations reporting 78% reduction in security incidents, 85% improvement in regulatory compliance scores, and 92% enhancement in employee trust metrics regarding data privacy protection. The framework's adaptability across various organizational sizes and industry sectors positions it as a scalable solution for contemporary HR technology challenges. Implementation challenges identified include resource allocation requirements, change management complexities, and the need for specialized cybersecurity expertise in HR technology domains. The research contributes to the growing body of knowledge on HR technology security by providing a comprehensive, evidence-based framework that balances operational efficiency with stringent security and privacy requirements. Future research directions include exploring artificial intelligence integration for predictive threat detection, examining cross-border data transfer compliance mechanisms, and investigating the impact of emerging technologies such as blockchain on HR data security. The framework serves as a foundational resource for organizations seeking to enhance their HR analytics capabilities while maintaining robust cybersecurity postures and ensuring comprehensive data privacy compliance.
Keywords: Human Resource Analytics; Cybersecurity Framework; Data Privacy Compliance; Workforce Information Systems; Zero-Trust Architecture; GDPR Compliance; HR Technology Security; Digital Workforce Protection